MARRIAGE AND JAVA’S TABOOS - Muh. Yusrol Fahmi; M. Luqman Hakim; Aina Noor Habibah; Sustika Wati (Bahasa Indonesia, 2023)
Javanese society has many taboos in determining marriage. The taboos are when someone chooses a marriage partner, some are happened in the marriage procession. Although these taboos are not written down and there is no guideline, but most of these taboos still exist in the Javanese society. Because there is no written text to discuss this issue, this concise article will discuss the taboos on marriage in Java. This research method uses an anthropological approach which is a field study by taking the facts. The results of this study conclude that there are at least two models of marriage taboos in Java, namely the taboo of choosing a mate and the taboo of choosing marriage day. The taboos of choosing a mate are katon omahe, weton, turun telu, jilu, geyeng, nyebrang kali, dandang angok-angok, sunduk wuwung, ngalor ngulon, kebo mbalik kandange, dadung kepluntir, two siblings (different gender) getting married with someone in the one village and nglangkahi mas e. Afterwards the taboos of choosing marriage day area marriage moment with the siblings having the same gender, marriage in the suro and selo (suro and selo are the months of Java), and marriage coincides with nas e mbah e.